THE DEVELOPMENT OF CAPACITIES OF LANGUAGE OF STUDENTS OF BASIC EDUCATION FOR THE TEXTUAL PRODUCTION OF THE GENRE DISCUSIVE/TEXTUAL WONDERFUL TALE (PERcursos Linguísticos, 2020)
This work aims to present the language capacities that students of the 6th grade of elementary school, developed for the textual production of the genre discursive/textual wonderful tale, when they participate in a pedagogical intervention process, constructed with support of the methodology of the didact sequence of genres. The construction of the genre became a semiotic instrument for the students language action in communicative situations in which the themeaning is related to discussing, to reflect on social problems that are establish in human relation.